A hybrid fuzzy-based approach for identifying global logistics strategies - Sheu, JB (My University, 2004)
This paper presents a hybrid fuzzy-based method that integrates fuzzy-AHP and fuzzy-MADM approaches for identifying global logistics (GL) strategies when corresponding supply and demand environments are complicated and uncertain. Before applying the methodology, six typical types of GL strategic modes were specified with their distinctive channels of physical distribution and information flows. Survey data collected from integrated circuit (IC) manufacturers in Taiwan was used to demonstrate the applicability of the proposed method. The empirical results indicate that the proposed method can be used to identify GL strategies when the factors that influence GL are complex and uncertain. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: global logistics; fuzzy-AHP; fuzzy-MADM; production research; transportation